Games in the countries of the Islamic Maghreb, their ways and methods for recreation (448-918 AH / 1056-1512 AD) Equestrian, horse racing and scepter as a model (Journal of Studies in History and Archeology, 2023)
The games that the countries of the Islamic Maghreb knew were not the result of their era, as they were passed down from generation to generation, but of course they were added to according to the divergence of ages and the passage of time. By making a living from it in addition to its basic work as self-entertainment and promotion from it, then its types multiplied and its means and innovations multiplied until it became an essential part of the life of different societies, and the Islamic Maghreb was not excluded in it and the nature of their dealings with it, so what are these games and what are their content and nature and the impact that they had on that society